História da educação matemática em arquivos da Escola Cidadã Integral Estadual de Ensino Fundamental e Médio Professor Luiz Gonzaga Burity no município de Rio Tinto – PB - Eustáquio, Gláuciely Eleutério (2018)
The present study aimed to conduct a comparative study among the mathematical contents taught at the Elementary and Middle Cittizen State School Luiz Gonzaga Burity Professor, from the decade of 1968 to 1978, with the contents currently taught in Mathematics. We used authors such as Valente (2007; 2013), Miguel and Miorim (2002) to understand the History of Mathematical Education, Medeiros (2003) and Franco (1984) to understand better the work with school record books, as well as Araújo (2017) that brings the history of Rio Tinto, site of the school researched. After a thorough categorization of the school archives documents, it was decided to research only with the 5th grade elementary school textbooks due to the large amount of documents found in the school archives, and also because the degree course in Mathematics of Federal University of Paraíba, Campus IV - North Coast, prepares the students to work in the final grades of elementary and middle school. The methodological course of the research is divided in two moments and consists of a documentary research, since it allows the study with primary sources such as: old books, textbooks, tests, legislation of that time, school record books, among others. As final considerations, we conclude that this research theme, that works with school archives of public institutions, is still little discussed, as well as in the History of Mathematics Education field, and that the contents present in school record books of about forty years are mostly repeated, and sometimes exceed the appropriate content we have for that year nowadays.